Mobitz type II atrioventricular block associated with tizanidine usein a patient with left ventricular hypertrophy: a case report - Hernández Navas, Jorge Andrés (2025)
A case is presented involving a 52-year-old woman with no significant medical history who attended a routine check-up. An initial electrocardiogram revealed left ventricular hypertrophy, prompting a 24-hour Holter monitor. This test showed the presence of supraventricular extrasystoles and episodes of second-degree atrioventricular (AV) block, type Mobitz II, which is unusual in an asymptomatic patient without structural heart disease. The patient was being treated with tizanidine for muscle pain, raising suspicion of a potential association between the medication and the transient AV block. Following the discontinuation of tizanidine, subsequent Holter monitoring demonstrated normalization of AV conduction. The patient remained stable and asymptomatic. This case highlights the importance of considering medication side effects, as second-degree AV block type Mobitz II can progress to more severe conditions.